Nanocrystal Assemblies: Current Advances and Open Problems - Lange Bassani, Carlos; van Anders, Greg; Banin, Uri; Baranov, Dmitry; Chen, Qian; Dijkstra, Marjolein; Dimitriyev, Michael S.; Efrati, Efi; Faraudo, Jordi; Gang, Oleg; Gaston, Nicola; Golestanian, Ramin; et al. (ACS nano, 2024)
We explore the potential of nanocrystals (a term used equivalently to nanoparticles) as building blocks for nanomaterials, and the current advances and open challenges for fundamental science developments and applications. Nanocrystal assemblies are inherently multiscale, and the generation of revolutionary material properties requires a precise understanding of the relationship between structure and function, the former being determined by classical effects and the latter often by quantum effects. With an emphasis on theory and computation, we discuss challenges that hamper current assembly strategies and to what extent nanocrystal assemblies represent thermodynamic equilibrium or kinetically trapped metastable states. We also examine dynamic effects and optimization of assembly protocols. Finally, we discuss promising material functions and examples of their realization with nanocrystal assemblies.
CRIS-Team Scopus Importer:2024-06-14
Keywords: assembly protocols; colloidal crystal; material properties; nanocrystal; nanocrystal assembly; nanoparticle; quantum dots; self-assembly; structure prediction; superlattice